Online Mathematics Learning in Tertiary Education: A Study on Students’ Behavior - Voon, Betty Wan Niu; Wong, Ling Shing; Siti Marhana, Razali (SAVAP International, 2014)
Learning mathematics requires extensive understanding and practical, which makes it a challenge to many students. Traditional face-to-face session with “chalk-andtalk” is still required for many students, who need extra guidance and step-to-step explanation on the subject. However, the advancement of digital technology today enable the teaching and learning on mathematics to be carried out through internet with less limitation in time and space. In this study, volunteered students were requested to take part in online mathematics learning activities. The students’ feedback indicated that with the blending of online approaches, improvement was achieved in learning the subject. In conclusion, students showed positive responses to the online mathematics study.